Facile Hydrazine‐Hydrothermal Syntheses and Characterizations of Two Quaternary Thioarsenates(III): Two‐Dimensional SrAg4As2S6⋅2 H2O and One‐Dimensional BaAgAsS3. Issue 12 (27th May 2016) - Yan, Dongming; Liu, Chang; Chai, Wenxiang; Zheng, Xuerong; Zhang, Luodong; Zhi, Mingjia; Zhou, Chunmei; Zhang, Qichun; Liu, Yi
Abstract: Two new quaternary thioarsenates(III), SrAg4 As2 S6 ⋅2 H2 O (1 ) and BaAgAsS3 (2 ), have been prepared through a hydrazine‐hydrothermal method at low temperature. Compound1 possesses a two‐dimensional (2D) layer network, while compound2 features a one‐dimensional (1D) column structure. The detailed structure analysis indicates that Sr 2+ and Ba 2+ cations have different directing effects on the structures of thioarsenates(III). Both experimental and theoretical studies demonstrate that compounds1 and2 are narrow‐gap semiconductors. Our success in synthesizing these two quaternary thioarsenates(III) proves that the hydrazine‐hydrothermal technique is a powerful yet facile synthetic method for exploring new complex chalcogenides with diverse crystal structures and interesting physical properties. Abstract : Two new quaternary thioarsenates(III), SrAg4 As2 S6 ⋅2 H2 O (1 ) and BaAgAsS3 (2 ), have been prepared through a hydrazine‐hydrothermal method at low temperature. Compound1 possesses a two‐dimensional (2D) layer network, while compound2 features a one‐dimensional (1D) column structure. The detailed structure analysis indicates that Sr 2+ and Ba 2+ cations have different directing effects on the structures of thioarsenates(III).